205k views
1 vote
X = y 2 - 1

2x - y = 4
Which of the following equations could be the result of using substitution to solve the system?

a. 2y 2 - y - 5 = 0
b. 2y 2 - y - 6 = 0
c. 2y 2 - 2y - 5 = 0

User Okon
by
5.9k points

1 Answer

1 vote
Your answer would be option B. 2y² - y - 6 = 0. This is because if you were to substitute x = y² - 1 into the equation 2x - y = 4, you would get 2(y² - 1) - y = 4, which expands into 2y² - 2 - y = 4, and then simplifies to 2y² - y - 6 = 0.
I hope this helps!
User AstroSharp
by
5.4k points